2022
DOI: 10.1002/app.52327
|View full text |Cite
|
Sign up to set email alerts
|

Biotin‐decorated redox‐responsive micelles from diselenide‐linked star‐shaped copolymers for the targeted delivery and controlled release of doxorubicin in cancer cells

Abstract: Polymeric micelles (s-PMs) assembled from star-shaped amphiphilic copolymers functionalized with cancer-homing molecules have been shown to have enormous potential to be used as a delivery tool to achieve longer half-life in the bloodstream, cancer-specific internalization, and controlled release of payloads in tumor cells. Considering the unprecedented thermodynamic stability of s-PMs owing to the entanglement of branched arms, we prepared a biotin-decorated and diselenide-linked star-shaped amphiphilic copol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…In another study, star-shaped redox-sensitive polymeric micelles were assembled from 3s-PCL-SeSe-PEG amphiphilic copolymer using ring opening reaction. 117 Biotin was further attached via its carboxylic group to the amino moiety of 3s-PCL-SeSe-PEG via DCC/NHS conjugation technique, then DOX was integrated into the targeted micellar core using dialysis or solvent exchange reaction. Physicochemical studies showed that the prepared nanomicelles were stable upon high dilution with redox-sensitive drug release profile in the high cancer redox environment.…”
Section: Polymeric Micelles For Targeting Different Receptorsmentioning
confidence: 99%
“…In another study, star-shaped redox-sensitive polymeric micelles were assembled from 3s-PCL-SeSe-PEG amphiphilic copolymer using ring opening reaction. 117 Biotin was further attached via its carboxylic group to the amino moiety of 3s-PCL-SeSe-PEG via DCC/NHS conjugation technique, then DOX was integrated into the targeted micellar core using dialysis or solvent exchange reaction. Physicochemical studies showed that the prepared nanomicelles were stable upon high dilution with redox-sensitive drug release profile in the high cancer redox environment.…”
Section: Polymeric Micelles For Targeting Different Receptorsmentioning
confidence: 99%
“…The intersection point of the vertical and horizontal tangent lines of the curve through the points of low concentration is considered as the CMC of the copolymer. 26,31 2.7. Preparation of Blank and DOX-Loaded Micelles.…”
Section: Synthesis Of Bi(hooc−peg-plga)-smentioning
confidence: 99%
“…It is based on the dilution of the micellar solution against a large volume of solvent, usually PBS, which represents the volume of the entire systemic circulation. 31 Thus, a 5 mg/mL micellar solution was prepared, and the volume was adjusted to 1000 folds by diluting with PBS. Then, the change in hydrodynamic diameter (D h ) as a function of time was measured in triplicate every 24 h for 7 days.…”
Section: Colloidal and Serum Stability Of Micellesmentioning
confidence: 99%
See 2 more Smart Citations